A three‐dimensional point process model for the spatial distribution of disease occurrence in relation to an exposure source. (26th May 2015) - Grell, Kathrine; Diggle, Peter J.; Frederiksen, Kirsten; Schüz, Joachim; Cardis, Elisabeth; Andersen, Per K.
<x xml:space="preserve">Abstract</x> We study methods for how to include the spatial distribution of tumours when investigating the relation between brain tumours and the exposure from radio frequency electromagnetic fields caused by mobile phone use. Our suggested point process model is adapted from studies investigating spatial aggregation of a disease around a source of potential hazard in environmental epidemiology, where now the source is the preferred ear of each phone user. In this context, the spatial distribution is a distribution over a sample of patients rather than over multiple disease cases within one geographical area. We show how the distance relation between tumour and phone can be modelled nonparametrically and, with various parametric functions, how covariates can be included in the model and how to test for the effect of distance. To illustrate the models, we apply them to a subset of the data from the Interphone Study, a large multinational case‐control study on the association between brain tumours and mobile phone use. Copyright © 2015 John Wiley & Sons, Ltd.